Study of Irisin Level Hormone and Some Biochemical Parameters in Iraqi Diabetic Type 2 without Hypothyroidism - Huda Amjad Hashim, Nawal.M.J. Al-Shammaa, (Pakistan Journal of Medical & Health Sciences, 2022)
This case-control study's purpose is to investigate serum irisin. levels and their role in people with type 2 diabetes mellitus (T2DM) who don't have hypothyroidism. A total of 60 patients with T2DM were chosen as the) case group (based on the grounds for inclusion and exclusion, and a 1:1 ratio was determined based on the patients' inclusion rate. This cohort, which was created at the Medical City / Baghdad Teaching Hospital, consisted of adults aged 30 to 60. The control group consisted of 60 healthy volunteers of the same gender and age. Clinical data on the participants was collected in order to determine their medical history, BMI, fasting blood glucose (FBS), hemoglobin (HbA1c), insulin, and serum lipid levels. An enzyme-linked immunosorbent test was used to measure the amount of irisin in the blood (ELISA). The data was analyzed using SPSS 23.0 software. only one variable. The amount of irisin in the T2DM group was substantially higher than in the control group (12.77±2.236 ng /mL and 4.121±0.308 ng /mL, respectively, according to single factor analysis. BMI, fasting blood sugar (FBS), HbA1c, insulin, total cholesterol (TC), and triglyceride (TG) levels were all higher with statistically significant differences, the T2DM group outperformed the control group.